2021
DOI: 10.3390/genes12070954
|View full text |Cite
|
Sign up to set email alerts
|

FABP2 Ala54Thr Polymorphism and Post-Training Changes of Body Composition and Biochemical Parameters in Caucasian Women

Abstract: The functional FABP2 Ala54Thr polymorphism (rs1799883) is strongly associated with lipid and carbohydrate metabolism, although the function of its potential modifying effect on training-induced changes in obesity-related parameters is still unknown. The aim of the present study was to investigate the influence of the Ala54Thr polymorphism on post-training changes of selected body mass and body composition measurements, as well as with biochemical parameters of energy metabolism. Accordingly, alleles and genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Our earlier findings confirm that the carriers of the Thr54 allele had higher BMI compared with the Ala54 carriers, suggesting that the Thr54 variant is a risk allele engaged in excess body mass in Polish women. On the other hand, we did not found evidence of a relationship between the FABP2 Ala54Thr polymorphism and physical activity on the selected body mass measurements as well as with biochemical parameters [76]. These results are consistent with Han [81], who showed that a 12-week regular aerobic training can beneficially prevent obesity-related traits; however, none of the examined parameters significantly changed across the FABP2 genotypes [81].…”
Section: Fabp2supporting
confidence: 84%
“…Our earlier findings confirm that the carriers of the Thr54 allele had higher BMI compared with the Ala54 carriers, suggesting that the Thr54 variant is a risk allele engaged in excess body mass in Polish women. On the other hand, we did not found evidence of a relationship between the FABP2 Ala54Thr polymorphism and physical activity on the selected body mass measurements as well as with biochemical parameters [76]. These results are consistent with Han [81], who showed that a 12-week regular aerobic training can beneficially prevent obesity-related traits; however, none of the examined parameters significantly changed across the FABP2 genotypes [81].…”
Section: Fabp2supporting
confidence: 84%
“…Indeed, genetic variants represent a substantial fraction of individual variation in lipid concentrations [ 3 ]. However, several articles focusing on the role of genetic variation in anthropometric and body composition parameters have revealed genetic markers that influence the functional response of the human body to regular physical activities [ 4 , 5 ], the legacy of these parameters remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported the importance of the following genes and their polymorphisms in fat loss: FTO , melanocortin 4 receptor ( MC4R ), peroxisome proliferator-activated receptor gamma ( PPARG ), peroxisome-proliferator-activated receptor delta ( PPARD ), PPARG coactivator 1 alpha ( PPARGC1A ), leptin ( LEP ), leptin receptor ( LEPR ), adiponectin, C1Q and collagen-domain-containing ( ADIPOQ ), adrenoceptor beta 2 ( ADRB2 ), adrenoceptor beta 3 ( ADRB3 ), insulin induced gene 2 ( INSIG2 ), and fatty-acid-binding protein 2 ( FABP2 ) (comprehensively reviewed in [ 22 ]). These data also show that the effectiveness of physical exercise on fat loss and improvement of aerobic capacity varies considerably between individuals [ 11 , 23 , 24 ]. This also means that shedding fat and changes in obesity-related traits in response to training programs may be more effective for some genotypes than others.…”
Section: Introductionmentioning
confidence: 97%